Observations from the field: interviewers' experiences interviewing and retaining homeless and vulnerably housed participants in longitudinal health research. Issue 2 (3rd July 2017) - Gerlitz, Julia; Joyce, Roxanne; Gadermann, Anne M.; Hubley, Anita M.; Ma Zhu, Sophie; Stowe, Meagan; Palepu, Anita
ABSTRACT: Conducting longitudinal research with homeless or vulnerably housed (HVH) participants is challenging. Homelessness, poverty, mental health issues, and addiction are social issues with which most cities in North America are grappling today. The study purpose was to explore the experiences of, and lessons learned by, staff in interviewing and retaining HVH adults in a marginalized neighborhood over the course of a 4 year longitudinal study. Four frontline interviewers from the Vancouver Health and Housing in Transition research team participated in six focus group sessions. Content analysis of transcriptions revealed three dominant themes: tracking and retention strategies; interviewer training and support; and interview dynamics. Participants' mental health and substance use impacted all stages of the research. Interviewers' experiences, observations, and recommendations contribute to the literature on interviewing and retaining HVH adults in longitudinal research as well as the training and support of staff.